Identifikasi Kandungan Kolesterol pada Udang Kelong Basah Menggunakan Metode Gas Chromatography-Mass Spectroscopy (GC-MS) - Yasser, M (INTEK: Jurnal Penelitian, 2017)
This study aims to identify the content of cholesterol in Kelong shrimp that have been preserved with ice cubes. The identification of cholesterol is done using Gas Chromatography-Mass Spectroscopy (GC-MS). The result of Chromatograms from analysis using GC-MS that has been compared to a standard cholesterol showed that shrimp Kelong which have been preserved ice cubes contain cholesterol.